Attosecond Light Pulses for Probing Two-Electron Dynamics of Helium in the Time Domain - Morishita, Toru; Watanabe, Shinichi; Lin, C. D. (My University, 2007)
Using attosecond light pulses to doubly ionize a two-electron wave packet of helium, we showed that the time-resolved correlated motion of the two electrons can be probed by measuring their six-dimensional momentum distributions. For simple wave packets, we showed that the measured momenta, when analyzed in appropriate coordinates, can reveal the stretching, the rotational, and the bending vibrational modes of their joint motion in momentum space, in spite of the Coulomb distortion in the final states.